(untitled) (Research, Society and Development, 2022)
The Cannabis sativa plant became known for being used to obtain the sensations of excitement and relaxation that substances from its flowers are able to provide. One of them is Cannabidiol, a non-psychoactive compound that has several therapeutic properties. Objective: To analyze studies that elucidate the Epidermal Endocannabinoid System (EES) and the anti-inflammatory property of Cannabidiol in the skin, thus identifying the benefits of using Cannabidiol in less invasive therapeutic treatments for acne vulgaris caused by Cutibacterium acnes. Methodology: To make this possible, an integrative literature review was carried out in the following databases: Scientific Electronic Library Online (SciELO), Google Scholar and PubMed, using the descriptors Cannabis sativa, Cannabidiol, Acne Vulgaris, Cosmetics and Pharmacological therapy. Results: In vitro and in vivo studies and research indicate that Cannabidiol has anti-inflammatory activity on the skin and has the potential to be manipulated as a topical cosmetic to prevent and combat acne caused by bacteria, without causing harm to the patient. Conclusion: Although its therapeutic activity has been verified, more studies in relation to the active need to happen. Meanwhile, its use remains just a hope for future alternative treatments for acne vulgaris, given that the substance is part of a plant that is still criminalized.